Liberal Neutrality: Constructivist, not Foundationalist - Horne, Lendell (Les ateliers de l'éthique / The Ethics Forum, 2009)
In defending the principle of neutrality, liberals have often appealed to a more general moral principle that forbids coercing persons in the name of reasons those persons themselves cannot reasonably be expected to share. Yet liberals have struggled to articulate a non-arbitrary, nondogmatic distinction between the reasons that persons can reasonably be expected to share and those they cannot. The reason for this, I argue, is that what it means to “share a reason” is itself obscure. In this paper I articulate two different conceptions of what it is to share a reason; I call these conceptions “foundationalist” and “constructivist.” On the foundationalist view, two people “share” a reason just in the sense that the same reason applies to each of them independently. On this view, I argue, debates about the reasons we share collapse into debates about the reasons we have, moving us no closer to an adequate defense of neutrality. On the constructivist view, by contrast, “sharing reasons” is understood as a kind of activity, and the reasons we must share are just those reasons that make this activity possible. I argue that the constructivist conception of sharing reasons yields a better defense of the principle of neutrality.